2004
DOI: 10.1158/0008-5472.can-03-3602
|View full text |Cite
|
Sign up to set email alerts
|

Interferon Regulatory Factor-1 Mediates the Proapoptotic but Not Cell Cycle Arrest Effects of the Steroidal Antiestrogen ICI 182,780 (Faslodex, Fulvestrant)

Abstract: Antiestrogens induce both cytostasis (cell cycle arrest) and apoptosis, but the relationship between these end points and the signaling that regulates their induction are unclear. We have previously implicated the transcription factor and putative tumor suppressor IFN regulatory factor-1 (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
75
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(84 citation statements)
references
References 56 publications
8
75
0
1
Order By: Relevance
“…The underexpressed set was found to be enriched in TFBSs principally of the interferon regulatory transcription factor (IRF) family (Figure 4a). Notably, IRF1 activity was previously demonstrated to be critical in response to endocrine therapies through promoting apoptosis (Gu et al, 2002;Bouker et al, 2004;Bowie et al, 2004). In contrast, the overexpressed set principally showed enrichment in E2Fs and SP1 TFBSs (Figure 4a).…”
Section: Effect Of 17be2 Through Eramentioning
confidence: 82%
“…The underexpressed set was found to be enriched in TFBSs principally of the interferon regulatory transcription factor (IRF) family (Figure 4a). Notably, IRF1 activity was previously demonstrated to be critical in response to endocrine therapies through promoting apoptosis (Gu et al, 2002;Bouker et al, 2004;Bowie et al, 2004). In contrast, the overexpressed set principally showed enrichment in E2Fs and SP1 TFBSs (Figure 4a).…”
Section: Effect Of 17be2 Through Eramentioning
confidence: 82%
“…In models of apoptosis in solid cancer cell lines by chemotherapy, there seems to be a longer time course of apoptosis, and a less marked response than those seen by death-ligands, similar to our model. In one study, doxorubicin has been found to upregulate IRF-1 in ERÀ and ER þ breast cancer cell lines (Bouker et al, 2004), and therefore it is possible that IRF-1 can mediate the ligand-independent FADD/caspase-8-mediated apoptosis seen with certain chemotherapeutics.…”
Section: Irf-1 Induces Ligand-independent Fadd-mediated Apoptosismentioning
confidence: 99%
“…IRF-1 not only induces apoptosis, but is also a necessary mediator of apoptosis for agents against breast cancer including Mullerian inhibiting substance (MIS) (Gupta et al, 2005), faslodex (Bouker et al, 2004), and in E6 expressing HMECs, tamoxifen (Bowie et al, 2004) and reconstituted extracellular matrix (Bowie et al, 2006). Despite the expanding role of IRF-1 in mediating apoptosis by various agents, the mechanism of IRF-1-induced apoptosis has been largely unstudied.…”
Section: Introductionmentioning
confidence: 99%
“…IRF-1 has been implicated to be involved in ICI 182 780 anti-estrogen resistance in breast cancer (Gu et al, 2002). IRF-1 is induced by the estrogen agonist/antagonist, tamoxifen (Tam) and the pure estrogen antagonist, ICI 182 780 (Bouker et al, 2004;Bowie et al, 2004). Taken together, these observations support the role of IRF-1 signaling in mammary gland homeostasis and estrogen/anti-estrogen signaling.…”
Section: Introductionmentioning
confidence: 59%
“…IRF-1 can be induced by type II-IFN (IFN-g) (Romeo et al, 2002) and is known to participate in both p53-dependent and -independent apoptotic signaling (Tamura et al, 1995;Tanaka et al, 1996). Recently, IRF-1 was shown to participate in both type IFN-g and anti-estrogen ICI 182 780 p53-independent apoptotic signaling in human breast cancer cell lines (Bouker et al, 2004;Porta et al, 2005). Taken together, these observations suggest that IRF-1 plays a role in p53-independent apoptotic signaling in mammary epithelial cells.…”
Section: Introductionmentioning
confidence: 99%